2015
DOI: 10.1097/mej.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of renal point of care ultrasound to detect hydronephrosis in children with a urinary tract infection

Abstract: The objective of this study was to investigate the accuracy of renal point of care ultrasound (POCUS) for the detection of hydronephrosis in children with a urinary tract infection (UTI). We prospectively included all patients with a final diagnosis of UTI who visited our pediatric emergency department between November 2009 and April 2011. Emergency physicians were encouraged to perform a renal POCUS during these visits, and a follow-up renal ultrasonography was performed by a radiologist who was blinded to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…in % (95% CI)Sp. in % (95% CI)LR+ (95% CI)LR− (95% CI) Hydronephrosis/nephrolithiasis Wong et al [ 113 ] EP 2018 MA ( 9 ) NR 1773 35 – 84 NR CT, visualisation of stone or surgical findings 70.2 ( 67.1 – 73.2 ) 75.4 ( 72.5 – 78.2 ) 2.85 0.39 Javaudin et al [114]EP2017France16 h.503847Radiologist US100 (82–100)71 (52–86)3.4 (2.0–6.0)0Pediatric hydronephrosis in UTIGuedj et al [115]EP2015France2 h.38259 m.Radiologist US76.5 (58.1–94.6)97.2 (95.2–99.2)27.30.25Scrotal pathologyBlaivas et al [118]EP2001USANR365845Radiologist colour doppler US95 (78–99)94 (72–99)16 a 0.053 a CholelithiasisEsquerrà et al [121]GP2012Spain212 h.11556NRRadiologist US88.9 (83.2–94.6)100 (NR)∞ a 0.111Lindgaard and Risgaard [9...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in % (95% CI)Sp. in % (95% CI)LR+ (95% CI)LR− (95% CI) Hydronephrosis/nephrolithiasis Wong et al [ 113 ] EP 2018 MA ( 9 ) NR 1773 35 – 84 NR CT, visualisation of stone or surgical findings 70.2 ( 67.1 – 73.2 ) 75.4 ( 72.5 – 78.2 ) 2.85 0.39 Javaudin et al [114]EP2017France16 h.503847Radiologist US100 (82–100)71 (52–86)3.4 (2.0–6.0)0Pediatric hydronephrosis in UTIGuedj et al [115]EP2015France2 h.38259 m.Radiologist US76.5 (58.1–94.6)97.2 (95.2–99.2)27.30.25Scrotal pathologyBlaivas et al [118]EP2001USANR365845Radiologist colour doppler US95 (78–99)94 (72–99)16 a 0.053 a CholelithiasisEsquerrà et al [121]GP2012Spain212 h.11556NRRadiologist US88.9 (83.2–94.6)100 (NR)∞ a 0.111Lindgaard and Risgaard [9...…”
Section: Resultsmentioning
confidence: 99%
“…One study not included in this meta-analysis found 100% sensitivity, but moderate specificity [114]. A French study found that EPs correctly identified hydronephrosis in children with urinary tract infections (prevalence = 5%) with a sensitivity of 76.5% and a specificity of 97.2% [115]. Finally, one large ( n = 2759) study, randomising patients into diagnosis through EP PoCUS, radiologist ultrasound or computed tomography (CT), found no difference in high-risk diagnoses that could be due to missed or delayed diagnosis after 30 days, and showed overall lower cumulative radiation exposure at 6 months for both ultrasound groups compared to the CT group [116].…”
Section: Resultsmentioning
confidence: 99%
“…80 In pediatric patients, the cornerstone for the evaluation for hydronephrosis is radiology-performed ultrasound. Guedj et al 81 patients with nephrolithiasis, the goal is to evaluate for the presence of hydronephrosis secondary to an obstructing stone. Radiology-performed ultrasound has been shown to be 66.7% sensitive (95% CI: 48.8% to 80.8%) and 97.4 specific (95% CI: 86.8% to 99.9%) for detecting stones, with a falsenegative rate of 59%.There is a paucity of pediatric-specific literature in which researchers assessed suspected nephrolithiasis, particularly in comparison with CT. 82,83 Although imaging may not be necessary in the acute setting, POCUS could be a useful screening tool for hospitalized patients who fail to respond to medical management.…”
Section: Renal and Bladdermentioning
confidence: 99%
“…Une étude a comparé l'échographie faite par un urgentiste et un radiologue pour la détection d'une dilatation rénale. Les RV+ et RV-de l'échographie faite par l'urgentiste sont respectivement de 27 et 0,2 [70]. Pour autant, l'échographie rénale est peu sensible pour le diagnostic d'anomalies rénales comparée à la cystographie [71].…”
Section: éChographie Interventionnelleunclassified